The “Psychological” Contract of Employment: A Qualitative Analysis of Psychological Contract Violation Within English Professional Rugby Union - Mike Rayner (Journal of Applied Sports Management, 2018)
Recent research illustrates that violated psychological contracts within the sports industry can have negative consequences on organisational relationships and productivity (Barnhill & Turner, 2014; De Ruiter, Schalk, Schaveling, & van Gelder, 2016; Matthijs Bal, Chiaburu, & Jansen, 2010; Nichols, 2013). While these studies contextualise the significance of the psychological contract to organisational behaviour and volunteer practices, little is known with regard to the impact of psychological contract violation within the professional sports industry. Therefore, this study explored qualitatively how psychological contract violation affects attitudes, behavior, and organisational performance of professional rugby union players’ within England. The results illustrate that psychological contract violation has a significant attachment to the concept of “marquee” signings that are allowed outside of the salary cap in professional rugby union within England, while also illustrating a relational psychological contract amongst the professional players despite the evident lack of any long-term contracts in the sport. Consequently, these results illustrate that effective management of the psychological contract should be a core component of human resource practices within professional rugby union. Subscribe to JASM
Keywords: Psychological contracts; Rugby Union; professional sport